Evaluation of the Total Thrombus-Formation System (T-TAS): application to human and mouse blood analysis. (3rd October 2019) - Al Ghaithi, Rashid; Mori, Jun; Nagy, Zoltan; Maclachlan, Annabel; Hardy, Lewis; Philippou, Helen; Hethershaw, Emma; Morgan, Neil V.; Senis, Yotis A.; Harrison, Paul
Abstract: The Total Thrombus-formation Analyser System (T-TAS) is a whole blood flow chamber system for the measurement of in vitro thrombus formation under variable shear stress conditions. Our current study sought to evaluate the potential utility of the T-TAS for the measurement of thrombus formation within human and mouse whole blood. T-TAS microchips (collagen, PL chip; collagen/tissue thromboplastin, AR chip) were used to analyze platelet (PL) or fibrin-rich thrombus formation, respectively. Blood samples from humans (healthy and patients with mild bleeding disorders) and wild-type (WT), mice were tested. Light transmission lumi-aggregometer (lumi-LTA) was performed in PRP using several concentrations of ADP, adrenaline, arachidonic acid, collagen, PAR-1 peptide and ristocetin. Thrombus growth (N = 22) increased with shear within PL (4:40 ± 1.11, 3:25 ± 0.43 and 3:12 ± 0.48 mins [1000, 1500 and 2000s −1 ]) and AR chips (3:55 ± 0.42 and 1:49 ± 0.19 [240s −1 and 600s −1 ]). The area under the curve (AUC) on the PL chip was also reduced at 1000s −1 compared to 1500/2000s −1 (260 ± 51.7, 317 ± 55.4 and 301 ± 66.2, respectively). In contrast, no differences in the AUC between 240s −1 and 600s −1 were observed in the AR chip (1593 ± 122 and 1591 ± 158). The intra-assay coefficient of variation (CV) (n = 10) in the PL chip (1000s −1 ) and AR chip (240s −1 ) were T10 14.1%, T60 16.7%, T10-60 22.8% and AUC10 24.4% or T10 9.03%, T80 8.64%, T10-80 23.8% and AUC30 5.1%. AR chip thrombus formation was inhibited by rivaroxaban (1 µM), but not with ticagrelor (10 µM). In contrast, PL chip thrombus formation was totally inhibited by ticagrelor. T-TAS shows an overall agreement with lumi-LTA in 87% of patients (n = 30) with normal PL counts recruited into the genotyping and phenotyping of platelet (GAPP) study and suspected to have a PL function defect. The onset (T10 ) of thrombus formation in WT mice (N = 4) was shorter when compared to humans e.g. PL chip (1000s −1 ) T10 were 02:02 ± 00:23 and 03:30 ± 0:45, respectively). T-TAS measures in vitro thrombus formation and can be used for monitoring antithrombotic therapy, investigating patients with suspected PL function defects and monitoring PL function within mice.